Analisis pendapatan dan tingkat efisiensi usahatani benih kentang granola (Solanum tuberosum L.): (Studi Kasus Di Ketua Kelompok Tani Mekar Setia Desa Margamukti Kecamatan Pangalengan Kabupaten Bandung) - Naficha Siti Rohmah; Ning Srimanganti; Dodi Tisna Amijaya; Edang Juliana Edang Juliana (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
Potato (Solanum tuberosum L.) is one of the types of vegetables that are widely grown in Indonesia. This study aimed to find out the prevalence of potato farming, the income value from potato seed farming through the calculation of farming costs and revenues, and the level of efficiency of potato seed farming in the head of the Mekar Setia farmer group. This research used the case study method and the analysis technique used is the descriptive analysis with a qualitative and quantitative approach with the sampling technique using primary data. In potato farming, the cost incurred on a land area of 1 ha is IDR204,242,044.00. The total revenue from the sale of consumption potatoes, seed potatoes, and rejection potatoes amounted to IDR512,000,000.00 so the income obtained was IDR307,757,956.00. The revenue/cost ratio obtained is 2.5 and with this value, it can be interpreted that the granola potato seed cultivation carried out by the Chairman of the Mekar Setia Farmers Group is profitable because from every one rupiah spent, it will get a revenue of 2.5 rupiah.